In search of model for evaluating the quality of e-commerce websites - Balfagih, Zain; Mohamed, Norshidah; Mahmud, Murni (2008)
The nature of e-commerce is diverse. E-commerce has been categorized into business-to-consumer (B2C), business-to-business (B2B), business-to-government (B2G), consumer-to-consumer (C2C) etc. Users of e-commerce websites may be consumers, software developers/ designers, business/ service providers, business partners, suppliers, governments etc. Researchers have also shown that there are several perspectives about evaluation on quality for e-commerce websites, that is, one may take an approach or combination of approaches like product quality, systems as product quality, service quality of provider, quality of service offered and quality of the Human Computer Interface (HCI) design. This paper documents the review of literature on models for evaluating the quality of e-commerce websites and argues that there is still a lack of research in the area because of the inherent diversity of e-commerce.